Potential Therapeutic Targeting Neurotransmitter Receptors in Diabetes - Pan, Xiaohui; Tao, Shibing; Tong, Nanwei (Frontiers in Endocrinology, 2022)
Neurotransmitters are signaling molecules in the nervous system. The pancreatic islets are hubs of glucose homeostasis that receives signals from both the central and peripheral nervous systems. Apart from nerve-origin signals, some neurotransmitters and/or their receptors are found in islets and are involved in the regulation of blood glucose, including amino acids, monoamines, acetylcholine and peptides. The endocrine cells in islets are able to synthesize and release insulin and glucagon with similar mechanisms used by neurons to maintain glucose homeostasis. Most transmitter receptors are G-protein coupled receptors (GPCRs), which couple with different G protein subunits to exert excitatory or inhibitory effects on target cells. Dysfunction of transmitters and their receptors in islets is involved in the development of hyperglycemia and type 2 diabetes (T2D). Transmitter-targeted therapies for neural and mental diseases possibly influence glucose homeostasis by acting on transmitter receptors on islet cells. Physiological and pathological hypermetabolic conditions also bring extra stress to islets and increase the risks of T2D and other metabolic diseases. Research on transmitters and their receptors in target organs can extend our understanding of neural, mental and metabolic diseases and assist with the development of new neurologic and antipsychotic drugs with higher selectivity and fewer side metabolic effects. Therapies targeting different transmitter systems have great potential in the prevention and treatment of T2D and other metabolic diseases.